Refinement of Isoflurane Anesthesia Scavenging Method by Using Modified Prototypes and Personnel Monitoring Exposure Assessment in Vivarium (Journal of Laboratory Animal Science, 2024)
Anesthesia is an important procedure performed in laboratory animals as part of the experimental activity. A calibrated  vaporizer is recommended for precision delivery and efficient scavenging is an integral part of avoiding possible health  hazards for personnel involved in gas anesthesia. The vivarium facility is equipped with scavenging devices such as activated  charcoal canisters, spot extractors, fume hoods, and biosafety cabinets those are engineering controls used during isoflurane  anesthesia. A modified prototype was necessitated especially when rodent procedures were conducted on the table due to  a higher turnover in a barrier-maintained facility. Hence, a well-designed prototype with different shapes was developed  to improve the scavenging methods during long-term tabletop anesthesia procedures where numerous animals are handled  to complete the activities within the timeframe. The concentration of waste anesthetic gas was captured systematically  from 13 laboratory personnel at different intervals and analyzed for quantitative exposure assessment for isoflurane. The  results revealed that the waste anesthetic concentration captured for laboratory personnel was between 0.08 to 1.45 ppm.  This result is below the reported recommended laboratory concentration (0.23 - 3.40 ppm). Moreover, the Time Weighted  Average (TWA) personal exposure to isoflurane was found to be below the Health and Safety Executive (HSE) established  Workplace Exposure Limit (WEL)-TWA (8 hours) of 50 ppm. The National Institute for Occupational Safety and Health  (NIOSH) has a non-regulatory recommended exposure limit (REL) for halogenated agents (e.g., isoflurane) of 2 ppm  or 15 mg/m3 as a ceiling limit (over a sampling period not to exceed one hour) during anesthetic administration. The  Occupational Safety and Health Administration (OSHA) has not established a regulatory permissible exposure limit (PEL)  for anesthetic gases; therefore, 2 ppm is used as the exposure threshold. Since each laboratory research and environmental  conditions vary, it is important that exposure monitoring is performed at least one time to ensure isoflurane levels are less  than 2 ppm. Overall, the implementation of a newly developed prototype along with canisters and an intensive exposure  assessment was found to efficiently capture the waste anesthetic gas from induction chambers and surgical areas with nose cone where isoflurane is constantly delivered during anesthesia. The portable setup with active suction arms and flexible  hose connectors can be placed on a table and/or enclosure to reduce the occupational exposure of Isoflurane to laboratory  personnel and demonstrated that the prototype had improved the scavenging practices in the vivarium.
Keywords: Isoflurane anesthesia; Laboratory Animals; Waste anesthetic gas; Scavenging Methods; Occupational Health and Safety; Exposure Assessment